Developing Scramble-Based Learning Method to Increase Students’ Reading and Writing Comprehension - Gunawan, Dani (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
This study was directed to develop a learning technique, to analyze the obstacles faced by teachers in implementing the lesson, and to overcome the problems faced by teachers in enhancing elementary students’ reading and writing comprehension. In order to fulfill the mentioned goals, this study tried to use scramble-based learning technique. It was cconducted at SDN Gentra Masekdas 1, Kecamatan Tarogong Kaler involving 32 first grade students. A pilot study was conducted on 9 March 2017 for about 35 minutes. The first cycle started on 18 April 2017, while the second one was on 24 April 2017. It was found that there was an increasing trend after the implementation. The analysis proccess generated data as followed: during pilot study, eight students succeeded to reach the standard indicator with percentage of 25%. Cycle I generated 15 students with learning completion percentage of 46.8.%. And, during second cycle, there were 27 students who succeeded in reaching completion standard with completion percentage of 84.3%.